Research and Application of Temperature Load of Switchgear. Issue 1 (1st December 2022) - Yang, Ruibo; Li, Tong; Chen, Jiehua; Lin, Jingfeng; Mao, Lei; Wang, Mu
Abstract: Abnormal changes in the temperature and load current of the high-current switchgear will directly affect the reliable operation of the equipment. In order to effectively monitor the temperature of the switchgear and ensure the reasonable arrangement of temperature measurement sensors, this paper realizes the optimal arrangement of sensors and the temperature prediction of the switchgear through simulation and test of the switchgear. Firstly, Ansoft electro thermal simulation module is used for joint simulation, the change of temperature field and the heating of current carrying bus are analyzed, the test data of temperature change under different environmental conditions are obtained, and the relationship between the temperature sensor and the distance between the hot spot is mastered. Then the temperature load curves under different currents are obtained through the test, and the accuracy of the research results is verified by the combination of theoretical simulation and field test. The test results can not only provide guidance for the temperature sensor installation scheme of substation field operation and maintenance personnel, but also improve the stability of equipment operation.